"Stego-Analysis Chain, Session One" investigations on steganography weakness Vs stego-analysis system for multimedia file - Naji, Ahmed Wathik; Gunawan, Teddy Surya; Hameed, Shihab A.; Zaidan, B.B.; Zaidan, A.A. (2009)

(untitled)
This paper give an overview on hidden data in a different carrier, in particular the paper overview different technique for steganography and giving a brief explain about each one, in order to implements stego-analysis system, this paper highlight the weak on the hidden data technique(disadvantage, weak point, type of attacker, stage of attacking the massage, etc) this paper also appoint the name of attackers on the data hidden and the passable way they follow for against that data, the review have gone through the characterization of Steganography Systems, it also disscuses many features on this area, which it may somehow give proper idea about immplement some stego-analysis systems.